2018
DOI: 10.1016/j.ijbiomac.2018.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between structurally different heteroexopolysaccharides and β-lactoglobulin studied by solution scattering and analytical ultracentrifugation

Abstract: Despite a very large number of bacterial exopolysaccharides have been reported, detailed knowledge on their molecular structures and associative interactions with proteins is lacking. Small-angle X-ray scattering, dynamic light scattering and analytical ultracentrifugation (AUC) were used to characterize the interactions of six lactic acid bacterial heteroexopolysaccharides (HePS-1-HePS-6) with β-lactoglobulin (BLG). Compared to free HePSs, a large increase in the X-ray radius of gyration R, maximum length L a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Previously, binding of BLGA and other prominent milk proteins to seven EPS from lactic acid bacteria has been assessed by surface plasmon resonance analysis, and the two EPS selected here bound most strongly to native BLGA, as demonstrated in that study . Generally, the interactions with purified milk proteins vary with EPS monosaccharide composition, glycosidic linkage patterns, branching, and molecular weight. Recently, it was suggested that the affinity for EPS is governed by polar interactions with only a smaller contribution from hydrophobic interactions and involves avidity between sites. , However, as the large molecular size of EPS hampers structural characterization of the protein complexes, the role of distinct EPS structures and the mechanisms of EPS–BLG interactions are poorly understood.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previously, binding of BLGA and other prominent milk proteins to seven EPS from lactic acid bacteria has been assessed by surface plasmon resonance analysis, and the two EPS selected here bound most strongly to native BLGA, as demonstrated in that study . Generally, the interactions with purified milk proteins vary with EPS monosaccharide composition, glycosidic linkage patterns, branching, and molecular weight. Recently, it was suggested that the affinity for EPS is governed by polar interactions with only a smaller contribution from hydrophobic interactions and involves avidity between sites. , However, as the large molecular size of EPS hampers structural characterization of the protein complexes, the role of distinct EPS structures and the mechanisms of EPS–BLG interactions are poorly understood.…”
Section: Introductionmentioning
confidence: 74%
“…41−51 Recently, it was suggested that the affinity for EPS is governed by polar interactions with only a smaller contribution from hydrophobic interactions and involves avidity between sites. 41,51 However, as the large molecular size of EPS hampers structural characterization of the protein complexes, the role of distinct EPS structures and the mechanisms of EPS−BLG interactions are poorly understood.…”
Section: ■ Introductionmentioning
confidence: 99%